## Simplifying (x+2y)(x-2y)

The expression (x+2y)(x-2y) is a product of two binomials. We can simplify this expression using the **difference of squares** pattern.

### Difference of Squares Pattern

The difference of squares pattern states:
**(a + b)(a - b) = a² - b²**

### Applying the Pattern

In our case, we have:

- a = x
- b = 2y

Applying the difference of squares pattern, we get:

(x + 2y)(x - 2y) = x² - (2y)²

### Final Simplification

Simplifying further, we get:

**x² - 4y²**

Therefore, the simplified form of (x+2y)(x-2y) is **x² - 4y²**.